Abutment Stability Analysis of Earthquake Load At Wawolatoma Bridge Latoma Sub-District Konawe Regency - Villa Eva Delvia GS; Putra Sakti (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
In this increasingly modern era, human needs are also growing. These need to be supported by adequate transportation infrastructure and can help. The stability against shear was obtained by the value of Rh = 235.20 kN and the importance of active earth pressure (Pa) = 96.08 kN so that the safety factor against shear was obtained from the division between the Rh value divided by the Pa value, a matter of 2.45 was brought. Why, Thishere this value more significant than the safety factor from shear, which is 1.? it can be concluded that stability against shear can be safe. Strength against overturning is obtained by comparing the moment of resistance of the structure as a support with the moment of turning that causes overturning (Mgl). With a value of Mw = 414.038 kN/m and agl = 179.36 kN/m, ana Fg an anna luan of 2.31 isobtainedwhichhch is where this value is greater than the safety factor for overturning, which is 1.5. From the calculation results, the ultimate bearing capacity value for the foundation on the surface (qu) is 292.76 kN/m, two, and the soil pressure to the bottom is evenly distributed (q'). Of 78.54 kN/m2.